2008
DOI: 10.1021/jp7119729
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Nitrosamines by Zeolite A:  Molecular Recognition in Subnanometer Space

Abstract: The adsorption and catalytic degradation of nitrosamines by zeolite A with cesium, potassium, sodium, or calcium cation was systemically studied in the research reported in this article. The results of instantaneous adsorption, temperature-programmed surface reaction, and in situ Fourier transform infrared spectroscopy measurements proved the adsorption of the bulky nitrosamines, N′-nitrosonornicotine (NNN) and Nnitrosopyrrolidine, on the zeolite A with a pore diameter of only 0.2-0.5 nm. Moreover, thermogravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 37 publications
(104 reference statements)
1
17
0
Order By: Relevance
“…13,14 Recent works include the numerical simulations of the exchange-dominated spin-wave spectra of two-dimensional (2D) MCs with line defects 15 and the theoretical investigation into point defects, and the coupling between them in 2D MCs. 16,17 Recently, Manzin et al modelled the influence of randomly distributed lattice defects on the ferromagnetic resonance behavior of 2D Ni 80 Fe 20 antidot arrays. 18 Compared to theoretical data on defect MCs (DMCs), experimental data on them are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Recent works include the numerical simulations of the exchange-dominated spin-wave spectra of two-dimensional (2D) MCs with line defects 15 and the theoretical investigation into point defects, and the coupling between them in 2D MCs. 16,17 Recently, Manzin et al modelled the influence of randomly distributed lattice defects on the ferromagnetic resonance behavior of 2D Ni 80 Fe 20 antidot arrays. 18 Compared to theoretical data on defect MCs (DMCs), experimental data on them are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…[56][57][58] Though both of the digestion methods were tried for the NOFs, the crystals were not completely dissolved in the DCl/D 2 O/DMSO-d 6 solution but were in the NaOD/D 2 O solution. The previous studies reported the digestion of post-synthetically modified MIL-125 or CAU-1 (isotopological Ti or Al frameworks of NOF-11 or 12, respectively) by NaOD/D 2 O or DCl/D 2 O/DMSO-d 6 solution for NMR measurements.…”
Section: Post-synthetic Nitrosationmentioning
confidence: 99%
“…The surface of LiCoO2 is coated with conductive materials such as silver 1 , carbon black 2 , carbon nanolayer 3 , multi-walled carbon nanotubes 4 and ionic liquids 5 , which can enhance the electric conductivity of the active materials.…”
Section: Introductionmentioning
confidence: 99%